Preclerkship medical students' perceptions of medical professionalism in the College of Medicine-University of Sharjah: A vision to sustain success in medical education - Mohamed Elhassan Abdalla; Nihar Ranjan Dash; Sarra Shorbagi; Mohamed H Ahmed (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Professionalism is an essential theme in both undergraduate and postgraduate medical education. The current study aimed to assess the preclerkship medical students' perception on medical professionalism. METHODS: A cross-sectional qualitative study using the critical incident technique was conducted at the University of Sharjah in the United Arab Emirates (UAE). An online survey was sent to 300 medical students (years 1-3). Participants were asked to describe an official doctor-patient encounter that they have experienced in a health-care setting and to highlight the professional behaviors in that encounter. They were then requested to list the top five characteristics of a professional doctor. Thirty (10%) medical students responded to the study; only 13 reported real incidents. The responses were independently reviewed by the authors. The descriptions of the professional attitudes were grouped according to the six domains of professionalism defined by the American Board of Internal Medicine (ABIM) Physicians Charter and then plotted against the nine domains of medical professionalism published in the UAE Consensus Statement. RESULTS: The most common professional behaviors reported were patience, honesty, respect, and patient care. The participants addressed all six domains of professionalism described by the ABIM physicians charter (altruism, accountability, duty , excellence, honor and integrity, and respect for others) and all the domains of medical professionalism published in the UAE Consensus Statement, except for "commitment to advocacy" and "commitment to education" domains. CONCLUSION: Preclerkship medical students had an insight about the professional behaviors needed from doctors before formal teaching about professionalism in the curriculum.